15. POSISI AMERIKA SERIKAT TERHADAP REZIM DASAR LAUT INTERNASIONAL OTORITA DASAR LAUT INTERNASIONAL - Arif Satrio Nugroho; Ika Riswanti Putranti; Andi Akhmad Basith Dir (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
International Seabed Authority came as an international organization that provided aregime to minimize the territory conflict that feared would be happened among states andminimizing environmental crime that would be occurred in international seabed area whichare beyond any national jurisdiction. As a part of UNCLOS and 1994 Agreement Part XI,the Authority was an international organization which duty is to manage seabed area thatlocated in international territory. But, in its development, United States as an activeparticipant of law of sea treaty development decided to decline the concept of InternationalSeabed Authority and reject the Authority as an international seabed regime until date.United States decided to not join International Seabed Authority and decline mining codeof the Authority as international seabed regime because of politic, economic, social andenvironmental factors which is less profitable if US joined the Authority. Meanwhile,international seabed regime that was built by the Authority is also not in line with USnational interest in international seabed management. Therefore, US established DSHMRA(Deep Seabed Hard Mineral Resource Act) as an alternative legal act to carry out theactivities in the Area. By DSHMRA, US interest in building the hegemony of seabedmanagement could be more facilitated.